Best Practice Penanaman Nilai Kemandirian melalui Pembelajaran Berbasis Proyek di SD - Theresia Indah Septalia; Gularso, Dhiniaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education, particularly the instillation of independence, is an important aspect in the development of elementary school students. However, in reality, there are still students who show low independence in learning, such as dependence on parents and teachers, lack of confidence, and low responsibility in completing tasks. This study aims to describe the implementation of Project-Based Learning and analyze its development in fostering independence among fourth-grade students at Kanisius Kalasan Elementary School. This study used a descriptive qualitative approach with teachers and 15 fourth-grade students as subjects. Data collection techniques included observation, interviews, and documentation during the implementation of a project on planting shallots using water as a medium in the subject of plants and their functions. The results showed that the application of Project-Based Learning was able to increase student active involvement and had a positive impact on the development of independence attitudes. Observation data showed an increase in students categorized as independent from 13% to 73%, as well as a decrease in students categorized as less independent from 67% to 7%. Project-based learning provides concrete, contextual learning experiences and encourages students to plan, implement, and take responsibility for the tasks assigned. Thus, Project Based Learning has proven to be effective not only in improving material comprehension, but also in instilling the value of independence in elementary school students in accordance with the independent dimension of the Pancasila Student Profile.